Pendampingan Penyusunan Laporan Keuangan Pada UMKM Rezeky Loundry Dengan Aplikasi “Akuntansiku” - Meesy Anugrah Putri; Siti Rodiah; Devinda Ramdani; Ameliya Ameliya (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Micro,Small and medium enterprises (MSMEs) in do not necessarily require financial assistance. Instead, they are encouraged to focus on enhancing their skills and resource capacity to address this issue. The objective of this article is to provide guidance for managing the financial statements of UMKM through a user-friendly tool called 'My Account'. This community project was conducted over a span of one week, utilizing methods such as observation, surveys, and direct interaction with customers. Information was gathered by directly engaging with the.The Rezeky Laundry Community Service initiative involves individuals who assist small and medium-sized enterprises in easily recording and compiling their financial reports. The main advantage of this service is the utilization of the "My Account" application, specifically designed for financial accounting purposes. This enables business partners of UMK to conveniently monitor cash inflows and outflows while also facilitating future repurchases.